(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
The aim of this paper is to present some architectural fragments found in the area of the “Terme Milano” in Gortys, Crete (director Prof. G. Bejor), in the light of the important data known after the excavations of 2010: the founding of a little limekiln. The architectural fragments found in leveling and filling strata may have been stored after the neglect of the construction site and not after the collapse of the buildings in which these pieces were initially used.